Selection of materials for IGBT modules to achieve stable short circuit failure behaviour - Li, Jianfeng; Yaqub, Imran; Johnson, Christopher Mark (2016)
IGBT modules which can fail to stable short circuit mode have great allocations in electricity network related fields. Sn3.5Ag solder joint and sintered Ag joint for the die attachment and Mo, Cu, Sn3.5Ag, Al and Ag foils for the top side insert material in the press pack like single IGBT samples have been investigated using overcurrent test plus current passage test. The results reveal that the Sn3.5Ag solder joint in combination with the Sn3.5Ag, Al or Ag foil can be employed to achieve the stable short circuit failure mode, and the best result is achieved with the Ag foil. This can be attributed to the formation of conductive networks / channels through the failed IGBT, and good mating between the insert material and the failed IGBT.